Disharmony Between Marriage Dispensation and the Sexual Violence Crime Law Number 12 of 2022 Concerning Marriage Coercion - Komarudin; Abdullah Musthofa (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to examine and analyze the disharmony between the marriage dispensation policy regulated in the Marriage Law and the provisions regarding forced marriage in the Sexual Violence Crime Law (TPKS Law) Number 12 of 2022. The marriage dispensation allows marriage under the ideal age while the law -non-violence laws try to prevent forced marriages from occurring. This research uses a juridical-normative approach with qualitative analysis methods. Data was collected through reviewing legal documents, case studies, and interviews with legal experts and social practitioners. The analysis focuses on inconsistencies between regulations that allow marriage dispensations and the protection of children from forced marriage as regulated in the Sexual Violence Crime Law. The research results show that there are legal implications that arise, namely Legal Uncertainty and secondly Violating the Principles of Justice and Legal Benefits. Meanwhile, the factors causing disharmony between the marriage dispensation and the sexual violence law are differences in objectives and philosophy and multiple interpretations of the two laws. This research concludes that it is necessary to synchronize and harmonize regulations between the Marriage Law and the Sexual Violence Crime Law to ensure more effective protection for children. The recommendations proposed include revising the marriage dispensation policy, increasing legal awareness among the community and law enforcement, as well as strengthening the role of child protection institutions in preventing forced marriage.